2012
DOI: 10.1007/s11464-012-0190-9
|View full text |Cite
|
Sign up to set email alerts
|

General techniques for constructing variational integrators

Abstract: The numerical analysis of variational integrators relies on variational error analysis, which relates the order of accuracy of a variational integrator with the order of approximation of the exact discrete Lagrangian by a computable discrete Lagrangian. The exact discrete Lagrangian can either be characterized variationally, or in terms of Jacobi's solution of the Hamilton-Jacobi equation. These two characterizations lead to the Galerkin and shooting-based constructions for discrete Lagrangians, which depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 25 publications
(26 reference statements)
0
74
0
Order By: Relevance
“…The choice of the Taylor method as the underlying one-step method has the advantage that it only requires one to precompute the prolongation of the Euler-Lagrange vector field once at the initial time, and the computational cost is not increased appreciably by having to compute the numerical solution at multiple quadrature nodes, since that only requires a polynomial evaluation. This efficiency in evaluation improves upon the methods outlined in [10] and [11], which utilized collocation and the shooting-method, respectively. Example 1.…”
Section: Lemmamentioning
confidence: 83%
See 1 more Smart Citation
“…The choice of the Taylor method as the underlying one-step method has the advantage that it only requires one to precompute the prolongation of the Euler-Lagrange vector field once at the initial time, and the computational cost is not increased appreciably by having to compute the numerical solution at multiple quadrature nodes, since that only requires a polynomial evaluation. This efficiency in evaluation improves upon the methods outlined in [10] and [11], which utilized collocation and the shooting-method, respectively. Example 1.…”
Section: Lemmamentioning
confidence: 83%
“…The simulations compare the discrete Lagrangian form of the Taylor variational integrator (TVI), the discrete right Hamiltonian form of the Taylor variational integrator (HTVI), the symmetric Taylor variational integrator of 4th order (SV4), Taylor's method, and the Runge-Kutta shooting variational integrators (ShVI) (see [11]). Overall, high-order Taylor methods perform quite well in terms of computational time versus global error.…”
Section: Comparison Of Methodsmentioning
confidence: 99%
“…Dealing with these issues, in their presentation of discrete mechanics, Marsden and West [39] defined an exact discrete Lagrangian L E d associated to any smooth Lagrangian L. They observed that if another discrete Lagrangian L d approximates the exact discrete Lagrangian to order p, then the corresponding discrete Hamiltonian flow that solves the discrete Euler-Lagrange equations, is order p accurate when used as a one-step numerical scheme to approximate smooth solutions of Euler-Lagrange equations. Leok and Shingel [35] develop a systematic method to construct discrete lagrangians (and variational principles) from smooth Lagrangians in mechanics, using a choice of a numerical quadrature formula, together with a choice of a finite-dimensional function space or a one-step numerical scheme. The order of the quadrature formula and numerical scheme determines the order of accuracy and momentum-conservation properties of the associated variational integrators.…”
Section: Proofmentioning
confidence: 99%
“…A systematic study is done for the case of covariant Lagrangian densities on a Lie group, using the exponential mapping, or the Cayley transform on SO(3) as retraction mapping (the latter improves the computational cost, keeping the order of accuracy), and fixing an arbitrary quadrature rule with several nodes. In [46] it is suggested that this variational error analysis may be extended to discrete field theories, and that one may develop general techniques for constructing variational integrators for field theories, extending in this way the theory of variational error analysis introduced by [39] and explored in [35], among others. Moreover [46] also remarks that a corresponding theory of variational error analysis for the discretization of field theories may also rely on a deeper understanding of the associated boundary Lagrangians and how they serve as generating functionals for multisymplectic relations.…”
Section: Proofmentioning
confidence: 99%
“…The essential aspects of VI's can be reviewed in Marsden and Wendlandt 1997; and in (Leok and Shingel 2012a;Leok 2005) general techniques for constructing variational integrators are provided. Spectral variational integrators are described in (Hall and Leok 2014a) and prolongation-collocation methods in (Leok and Shingel 2012b).…”
Section: Variational Integrationmentioning
confidence: 99%